Komunikasi: Nyata, Maya dan Hubungannya dengan Pendidikan - Primadi Tabrani (Wimba : Jurnal Komunikasi Visual, 2012)
Human communication is the topic of this article. It begins with Direct-Contact Communication in prehistory and during childhood. Than follows Distance-Communication that begins with talking, than writing and reading follows. Since the beginning there are always criticism every time a new communication media emerge. This criticism accelerate with the habit of indulging reading literature in the train, chatting by amateur radio and end up in BB's cyberspace and its facebook. Besides its positive effect, we are intoxicated by this IT communication. So we loose many productive hours of working time. The IT (Information Technology) becomes frightening with its "clever" CDs in general education and so is the training of skills and competency with the help of IT simulators. Are we educating real human or virtual humans? Is this excess of IT happening a common happening, a risk of being modern? Or are there somekind of education missing? How to overcome it?